The human ACE-2 receptor binding domain of SARS-CoV-2 express on the viral surface of the Newcastle disease virus as a non-replicating viral vector vaccine candidate - Bo-Kyoung Jung; Yong Hee An; Jin-Ju Jang; Joo Hee Jeon; Sung Hoon Jang; Hyun Jang (PLoS ONE, 2022)
Since the SARS-CoV-2 infection was identified in December 2019, SARS-CoV-2 infection has rapidly spread worldwide and has become a significant pandemic disease. In addition, human death and serious health problem caused by SARS-CoV-2 infection, the socio-economic impact has been very serious. Here, we describe the development of the viral vector vaccine, which is the receptor-binding domain (RBD) of SARS-CoV-2 expressed on the surface of Newcastle disease virus (LVP-K1-RBD19). The RBD protein concentrations on the viral surface were measured by the sandwich ELISA method. 106.7 TCID50/ml of LVP-K1-RBD19 has a 0.17 μg of RBD protein. Optical density (OD) values of mouse sera inoculated with 10 μg of RBD protein expressed on the surface of LVP-K1-RBD19 generated 1.78-fold higher RBD-specific antibody titers than mice inoculated with 10 μg RBD protein with alum at 28 dpi. Moreover, mice inoculated with 10 μg of RBD protein expressed on the surface of LVP-K1-RBD19 virus showed more than 80% neutralization at 1:256 against the SARS-CoV-2 pseudovirus. These results demonstrated that inactivated LVP-K1-RBD19 virus produces neutralizing antibodies against SARS-CoV-2 in a short period and could be elect protective immunity in humans and LVP-K1-RBD19 will be a good candidate for the COVID-19 vaccine.